Wellcome!

Question 1. Asked on :17 August 2019:05:57:38 PM

#### Find a quadratic polynomial , The sum and product of whose zeroes are -3 and 2 respectively.

-Added by Khushi Chauhan Mathematics » POLYNOMIALS

Himanshi Verma

Let the quadratic polynomial be ax2+bx+c=0 and its zeroes be α and β.

sum of zeroes     α+β = -3 = -b/a

product of zeroes      αβ = 2= c/a

If a=1   then b=3,  c=2

So, the quadratic polynomial is x2+3x+2.

-Answered by Himanshi Verma On 18 August 2019:11:00:35 AM

Akki chauhan

what is the polynomials.

-Answered by Akki chauhan On 24 August 2019:03:13:10 PM

Question 3. Asked on :27 January 2019:11:08:39 AM

#### (4-k)x2+(2k+4)x+(8k+1)=0.k=? एक पुर्ण वर्ग है ?

-Added by SURAJ KUMAR Mathematics » POLYNOMIALS

Himanshi Verma

The given quadratic will be a perfect square if it has two real and equal roots. To have two real and equal roots the discriminant must be zero.

i.e., b²-4ac=0

or, (2k+4)²-4(4-k)(8k+1)=0

or, 4k²+16k+16-4(32k-8k²+4-k)=0

o², 4k²+16k+16-128k+32k²-16+4k=0

or, 36k²-108k=0

or, 36k(k-3)=0

either 36k=0

or, k=0

or, k-3=0

or, k=3

∴, k=0,3 Ans.

-Answered by Himanshi Verma On 02 February 2019:01:43:20 PM

Question 4. Asked on :27 January 2019:10:59:13 AM

#### abx2+(b2ac)x-bc=0.सरल करे|

-Added by SURAJ KUMAR Mathematics » POLYNOMIALS

Himanshi Verma

Consider, abx2 +(b2-ac)x-bc = 0

⇒ abx2 + b2x – acx – bc = 0
⇒ bx (ax + b) – c(ax + b) = 0
⇒ (ax + b)(bx – c) = 0

-Answered by Himanshi Verma On 02 February 2019:01:44:13 PM

Question 5. Asked on :27 January 2019:10:54:59 AM

#### ax2+4ax+(a2-b2)=0

-Added by SURAJ KUMAR Mathematics » POLYNOMIALS

Question 6. Asked on :27 January 2019:10:51:05 AM

#### 1/a+b+x=1/a+1/b+1/x,a+b not equal 0.सरल करे |

-Added by SURAJ KUMAR Mathematics » POLYNOMIALS

Himanshi Verma

ON solving the above equation we have a quadratic equation

(a+b)x^2+(a+b)^2x+ab(a+b)

on solving the above equation by formula -b+root over(b^2-4ac) and -b-root over(b^2-4ac)

we got -a and -b as roots.

According to me this is much easier then others when compared.

-Answered by Himanshi Verma On 10 March 2019:04:49:29 PM

Question 7. Asked on :27 January 2019:10:46:14 AM

-Added by SURAJ KUMAR Mathematics » POLYNOMIALS

Akki chauhan

what is your question

-Answered by Akki chauhan On 30 August 2019:08:53:43 PM

Question 8. Asked on :12 January 2019:10:49:51 AM

#### Factorise:x3-23x2+142x-120

-Added by Akki chauhan Mathematics » Polynomials

Shivang Gupta

x-23x2+142x-120

=x3-x2-22x2+22x+120-120

=x2(x-1)-22x(x-1)+120(x-1)

=(x-1)(x2-22x+120)

=(x-1)(x2-12x-10x+120)

=(x-1)[x(x-12)-10(x-12)]

=(x-1)(x-10)(x-12)

-Answered by Shivang Gupta On 25 August 2019:05:08:24 PM

Shivang Gupta

When p(x) is divided by (x-2),

By remainder theorem,

Remainder= p(2)

p(2)=a*2^3 + 3*2^2 - 13

=a*8+3*4-13

=8a+12-13 = 8a-1

p(2) = 2*2^3-5*2+a

=2*8-10+a

=16-10+a = 6+a

Since the remainders of ax^3+3x^2-13 and 2x^3-5x+a are same when divided by x-2,

8a-1 = 6+a

8a-6+a=1

8a+8=1-6=-5

8a=-5-8 =-13

a=-13/8

-Answered by Shivang Gupta On 25 August 2019:05:08:54 PM

Question 10. Asked on :12 January 2019:10:38:50 AM

#### If a = 9-4√5, then find the value ofa2 + 1a2

-Added by Akki chauhan Mathematics » Polynomials

Master Purushottam

(a+1/a)2=a2+1/a2+2

a2+1/a2=(a+1/a)2-2→ I

Now,

a=9-4root5

1/a=1/9-4root5

=(1/9-4root5)×9+4root5/9+4root5

=(9+4root5)

a+1/a=9-4root5+9+4root5

=81

Now,

a2+1/a2=(a+1/a)2-2 →(from I)

=(81)2-2

=6561-2

=6559

-Answered by Master Purushottam On 22 August 2019:09:08:56 PM

Question 11. Asked on :11 January 2019:10:04:29 AM

#### What is Degree of the Polynomials?

-Added by Prince Rawat Mathematics » POLYNOMIALS

Shivang Gupta
Highest power of X in algebraic expressions is called the degree of polynomial.

-Answered by Shivang Gupta On 25 August 2019:03:29:51 PM

You can see here all the solutions of this question by various user for NCERT Solutions. We hope this try will help you in your study and performance.

This Solution may be usefull for your practice and CBSE Exams or All label exams of secondory examination. These solutions or answers are user based solution which may be or not may be by expert but you have to use this at your own understanding of your syllabus.

#### What do you have in your Mind....

Our Expert Team reply with answer soon.

* Now You can earn points on every asked question and Answer by you. This points make you a valuable user on this forum. This facility is only available for registered user and educators.

Next moment you answer is ready .... go ahead ...

## Search your Question Or Keywords

#### Do you have a question to ask?

User Earned Point: Select

## All Tags by Subjects:

Science (1310)
History (166)
Geography (143)
Economics (121)
Political Science (48)
Mathematics (145)
General Knowledge (3128)
Biology (69)
Physical Education (12)
Chemistry (25)
Civics (17)
Home Science (10)
Sociology (8)
Hindi (8)
English (145)
Physics (20)
Other (32)
Accountancy (11)